Socio-cultural Values of Whales in Húsavík and their Implications for Social-ecological Resilience - Sarah Seabrook Kendall 1993- (2021)
This study examines socio-cultural values related to whale ecosystem services in Húsavík, Iceland in the context of social-ecological shifts, like climate change and globalization, that are rapidly taking place in and around the Arctic. Húsavík is a municipality in Northern Iceland whose economy has been influenced by whale watching in recent years leading up to the COVID-19 pandemic. The benefits for community members associated with whales and whale watching in Húsavík have significant resilience implications in light of Húsavík’s vulnerability to climate change and globalization. To enhance understanding of resilience in Húsavík, this study uses grounded theory based qualitative content analysis of interviews with community members to a elicit a list of socio-cultural values of whale ecosystem services. The economic, educational, and social contributions of whale ecosystem services to the community were especially valued by those interviewed. Analysis of these values in the context of Húsavík’s vulnerability reveals significant contributions of whale-related socio-cultural values to various components of social-ecological resilience within Húsavík, including: human capital, institutions and services, economy, diversity, and education. Socio-cultural values of whale ecosystem services could aid place-based local climate adaptation efforts in Húsavík by informing community assessments. These assessments provide local context for understanding adaptation in a given place, in part by articulating how and why people value various parts of their social-ecological system. Given the importance of whales to Húsavík, whale-related socio-cultural values can further this aspect of adaptation planning and help preserve resilience and adaptive capacity within Húsavík. Þessi rannsókn skoðar félags- og menningarleg gildi vistkerfaþjónustu hvala í Húsavík, í samhengi við sviptingar í félags- og vistkerfum, eins og loftslagsbreytingar og hnattvæðing, sem umbreyta nú svæðum innan og nálægt norðurheimskautinu hratt. Húsavík er ...